2017
DOI: 10.1590/0102-33062017abb0179
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of miR156 and miR172 involved in the flowering of Jatropha curcas L.

Abstract: Jatropha curcas is a plant that accumulates high-quality oil in its seeds, which is capable of being transformed into liquid biofuel. However, several aspects of its fl owering are still unknown, which is a key step in the production of fruits, seeds, and oil. Flowering is a complex process that is regulated by various factors at the molecular level, including microRNAs (miRNAs). Th ere is evidence suggesting that the miRNAs of the miR156 and miR172 families play a key role in the fl owering transition of plan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 45 publications
1
1
0
Order By: Relevance
“…S1 ), and therefore, a pair of miR172a primers can detect the expression of all mature miR172s; qRT-PCR was performed with total RNAs extracted from various tissues. The results indicated that there was an age-related increase in miR172 expression in Jatropha ( Fig.�1B ), which is consistent with a recent study of dynamics of miR172s during a production cycle of Jatropha ( S�nchez-Guti�rrez et�al. 2018) .…”
Section: Resultssupporting
confidence: 92%
“…S1 ), and therefore, a pair of miR172a primers can detect the expression of all mature miR172s; qRT-PCR was performed with total RNAs extracted from various tissues. The results indicated that there was an age-related increase in miR172 expression in Jatropha ( Fig.�1B ), which is consistent with a recent study of dynamics of miR172s during a production cycle of Jatropha ( S�nchez-Guti�rrez et�al. 2018) .…”
Section: Resultssupporting
confidence: 92%
“…SPL4 is known to promote the transition to reproductive maturation in plants at least in part through activation of various floral identity genes [2527]. miR172 acts antagonistically to miR156 and is considered a positive regulator of flowering by repressing AP2 like floral repressor genes [24, 2830]. Transcript abundance of the AP2 homolog, PaRAP2.7B , was inversely correlated with miR172 and highly expressed in the seedling rootstocks and scions relative to clonal rootstocks and budwood scions (Fig.…”
Section: Resultsmentioning
confidence: 99%